Management of Antenatal Care Midwifery Care in Mrs. "O" with Hyperemesis Gravidarum Level I at Puskesmas Bara-Baraya Makassar from September 26, 2023 to November 13, 2023 - Nurhuzaifa; Salehah, Sitti; Andryani, Zelna Yuni; Diarfah, Andi Dian (Jurnal Midwifery, 2025)
Introduction Hyperemesis gravidarum is a condition in which pregnant women experience excessive vomiting, leading to weight loss, dehydration, starvation-induced acidosis. The exact cause is not yet known. However, there are several factors suspected to contribute to hyperemesis gravidarum in pregnant women, such as being a first-time mother (primigravida), having a history of mola-hydatidiform, or carrying twins/ multiple pregnancies. The research aimed to provide midwifery care for Mrs. 'O' with Hyperemesis Gravidarum of Level I at Bara-Baraya Health Center in Makassar from September 26th to November 13th, 2023. Method The method used was a case study which was appropriate to the client's needs and the midwife's authority, using midwifery care management approach of 7-step Varney and documentation in SOAP format. Result The results of the case study on Mrs. 'O' with Hyperemesis Gravidarum of Level I, a 38-year-old woman, revealed complaints of excessive vomiting, mostly in the morning, and her appetite began to decrease. After eight weeks of care, Mrs “O” no longer experienced vomiting, her appetite was good, and vital signs were within normal limits. The general condition of the Mrs “O” was good, with a compos-mentis consciousness level, normal vital signs, and no abnormalities found in the physical examination. Conclusion. In conclusion, the case study on Mrs. 'O' with Hyperemesis Gravidarum of Level I was well-conducted. Thus, the documentation of all findings and the actions given to Mrs. 'O' indicated no gaps.